Equilibrium of CO2 in aqueous diethanolamine (DEA) and Amino Methyl Propanol (AMP) solutions - Haji-Sulaiman, M.Z.; Aroua, Mohamed Kheireddine (Taylor & Francis, 1996)
Equilibrium data of CO2 in aqueous solutions of DEA and AMP for a range of CO2 partial pressure (0.5-100 kPa) and temperature (25-80Â°C) obtained using a stirred cell reactor is presented in this paper. The data were analyzed using the Deshmukh and Mather Model. It has been found that this model is able to predict results which are close to the experimental data in terms of the total CO2 loadings and the pH of the solution, an additional parameter which was monitored in this work. Comparison was also made with other published results using the different interaction parameters generated in this work. Good agreement between predicted and experimental values were also observed.